Region-based lossless data hiding with high capacity for medical images - Xiao-hong DENG; Zhi-gang CHEN; Di-qing LIANG; Yi-min MAO (Tongxin xuebao)
In view of the significant regional features of medical images,a new high capacity lossless data hiding method based on region and histogram shifting was presented.Firstly,the presented method utilized segmentation method of the maximum class separation distance to get the foreground region of medical images,and then used the polymeric polygonal approximation and image fitting algorithm to get the embedding region of region foreground.In the embedding procedure,the difference histogram circular shifting method and the code-based histogram shifting method were presented to embed hidden data in foreground and background region respectively,which improved the limit embedding capacity and resolved the overflow and underflow in traditional histogram shifting method.Experimental results show that the proposed method achieves high embedding capacity with 1 bit/pixel and stego-image quality about 40 dB.The presented method can be applied to the quality of sensitive image's large capacity information hiding with regional feature.